Åkerböna i samodling med vårvete som helgrödesensilage till mjölkkor - Haag, Therese (SLU/Dept. of Agricultural Research for Northern Sweden, 2007)
The aim of this undergraduate thesis was to formulate advices regarding the use of field beans, cultivated together with spring wheat, as whole-crop silage in feeding to dairy cows. In the thesis, optimal harvest time of the field bean/spring wheat crop, as well as the feeding value and the fermentation quality, was studied.